Contribution of worker participation to increase the efficiency of firms - P. De Villiers; G. Kooy (South African Journal of Business Management, 2004)
There are many factors that may lead to inefficiencies in a firm. One reason is the existence of a principal-agent problem. Linked with this problem is asymmetric information, unaligned motives of principals and agents, distrust (that was rampant in the era of apartheid in South Africa, but more recently the Basic Conditions of Employment Act can fulfil this role) and conflict. Worker participation schemes can help to alleviate this problem and different forms of worker participation schemes are discussed that can increase efficiency of firms.
Keywords: 650